TANTANGAN DIGITALISASI DAN PERGESERAN NILAI-NILAI BUDAYA TRANSFORMATIF ANAK USIA DINI - St Marwana Aisyah Marwa; Siska; Nurul Putri Ramadhani; Hajerah; Muhammad Akil Musi (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2026)
The current global challenge focuses on the role of digitalization, which increasingly leads to changes in transformative cultural values ​​for children. The purpose of this study is to describe the challenges of digitalization in shifting transformative-based cultural values ​​in early childhood. This study uses a Systematic Literature Review (SLR) through data analysis of 287 literature manuscripts. As well as sorting data based on the needs of research variables using 42 literature manuscripts, reviewed by the data retrieval process using 22 literature manuscripts that include research results and discussions that explain the shift in transformative cultural values ​​​​that have been inserted through AI (Artificial Intelligence)-based digital content. The content presented really shows the perfection of the design without any design that can differentiate non-AI-based content. In addition, the technological approach without rules and guidance by adults. Transformative-based cultural values ​​​​without conceptual filtering. Will affect children's ability to think impulsively, negative stimulus disorders (distractions) based on situations based on their imagination. A digital-based environment can dominate children's thinking, disrupting behavioral patterns in early childhood. However, current government regulations restrict access to digital technology for children under 16. This is a positive step taken by the government to protect children from the impact of shifting cultural values ​​caused by digitalization. The research suggests that parents should be more aware of the limitations of current technological developments, especially if technology has already taken over children's development.